Going upstream: a pluri-ontological analysis and proposal for Brazilian participatory water governance - Thomas Rickard; David Ludwig; Raoni Rajão (Ecosystems and People)
Despite the growing emphasis on ontological pluralism in environmental policy debates, innovation within national state environmental governance and management remains limited. This article outlines a conceptual framework for ontological inclusion and exclusion to examine constraints and opportunities in Brazilian participatory water governance. This involves an ontological policy cycle of the Suaçuí state river basin, a participatory process for water-body classification, and a water-body-classification instrument. River ontologies of the Suaçuí river basin and participatory process were found to be excluded from the water-body classification instrument through various practices and modes of exclusion. Relational ontologies, both indigenous and non-indigenous, were excluded. Building on the analysis of how ontological exclusion occurred, speculative design was engaged to critically imagine a pluralist ontological proposal. A database with diverse water inputs and outputs for more sustainable and inclusive planning is envisaged. This proposition grounds reflections on challenges for ontological inclusion in the context of political, economic, and social inequalities. Ontological inclusion and exclusion complement classic concepts of social and epistemic inclusion with distinct normative demands and propositions for established participatory environmental governance.